2010
DOI: 10.51724/ijpce.v2i1.180
|View full text |Cite
|
Sign up to set email alerts
|

Constructivist practices through guided discovery approach: The effect on students’ cognitive achievement in Nigerian senior secondary school physics

Abstract: The study investigated constructivist practices through guided discovery approach and the effect on students’ cognitive achievement in Nigerian senior secondary school Physics. The study adopted pretest-posttest control group design. A criterion sampling technique was used to select six schools out of nine schools that met the criteria. A total of 278 students took part in the study; this was made up of 141 male students and 137 female students in their respective intact classes. Physic Achievement Test (PAT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 3 publications
2
12
0
4
Order By: Relevance
“…The results indicated that it would not (see Table 2). This finding agrees with Akinbobola and Afolabi (2009), who found that there is no significant difference between the achievement of male and female students in physics who are taught with a guided-discovery teaching approach. The finding corresponds with Ogundola et al (2010) who also found no significant difference between male and female students exposed to the constructivist method.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results indicated that it would not (see Table 2). This finding agrees with Akinbobola and Afolabi (2009), who found that there is no significant difference between the achievement of male and female students in physics who are taught with a guided-discovery teaching approach. The finding corresponds with Ogundola et al (2010) who also found no significant difference between male and female students exposed to the constructivist method.…”
Section: Discussionsupporting
confidence: 91%
“…There are no indications in literature that males do better than females or vice versa in the context of constructivism. Although, some research suggests gender differentiation (Duyilemi & Bolajoko, 2014), others suggest that there is significant difference between the achievement of male and female exposed to a constructivist method (Akinbobola & Afolabi, 2009;Ogundola et al, 2010). This scenario extends to non-academic situations, for instance, in business and entrepreneurship (Wilson & Tagg, 2010).…”
Section: Constructivism As a Pedagogical Frameworkmentioning
confidence: 99%
“…Pembelajaran inkuiri merupakan suatu model yang memberikan kesempatan mahasiswa melakukan penyelidikan terhadap permasalahan IPA yang diminatinya (Ketpichainarong dkk., 2010). Model pembelajaran inkuiri sesuai dengan prinsip konstruktivistik, yaitu memberikan kesempatan siswa mengkonstruksi pemahaman baru berdasarkan pengalaman mereka mengeksplorasi berbagai fenomena di lingkungannya (Akinbobola & Afalobi, 2010;Andrini, 2016;Rahayu, 2016).…”
Section: Pendahuluanunclassified
“…Guided discovery can also be a very contributing method in helping the English learners to possess real chances of using the target language interactively. Such a finding is supported by the results of Akinbobola and Afolabi (2010). According to these researchers, the strategy of guided discovery learning enhances the academic achievement of the students compared to the traditional lecture process.…”
mentioning
confidence: 69%